Sungguh-Sungguh, Kontinuitas dan Cita-Cita Luhur Dalam Belajar Pada Kitab Ta'lim Muta'alim - Athifatul Nabila; Martyo Martyo (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
The Ta'lim Muta'alim discusses earnestness, continuity, and lofty ideals. In this chapter, it is recommended to aspire to be noble in knowledge and have sincerity in learning. The lofty ideals recommended in this chapter involve exerting one's utmost effort, supporting oneself, and avoiding laziness. The seeker of knowledge must be earnest and continuous in learning. On the other hand, in order for success to be achieved, it is necessary for all three parties: the student, the teacher, and the parents. Students should be able to learn and repeat lessons continuously. The approach used in this journal is library research, which is entirely a search for reading materials that are library in nature, recording, reading and analyzing books, articles, and literature that have a relationship with the title of the study in this journal.From the explanation above, it can be concluded that a student who is serious about his aspirations must learn by repeating knowledge continuously. Students should repeat knowledge at the beginning of the night and the end of the night because at that time there is a blessing for the one who learns. At night students will be able to concentrate because there are no crowds.